Meniti Sejarah Asal Mula dan Perkembangan Hukum dalam Masyarakat - Tjunggozali Joehana (Antropologi Indonesia, 1989)
In this article, the author describes and analyzes methods and approaches used by anthropologists in studying law since the end of 19th century. One of the main aims of anthropology, according to the author, is explaining the causal relation of law. This can be achieved by means of using the holistic approach. It should include the embeddedness of various aspects in the society's suprastructure, social structure, and infrastructure.